Estimation of Aggregate Consumption Function for Nepal: ARDL Bound Testing Approach - Chaudhary, Arbind (NRB Economic Review, 2017)
The relationship between aggregate consumption and its determinants is one of the oldest statistical regularities of macroeconomics. It is important for macroeconomists, policy makers and for others as well. This study aims to estimate aggregate consumption function for Nepal employing Autoregressive Distributed Lag Model (ARDL) for the period of 1975 to 2015 using real income, real exchange rate, real interest rate and inflation rate as determinants. ARDL based co-integration analysis finds the existence of long run association among the variables. Furthermore, elasticity coefficient of real income is found significantly positive but the coefficients of other variables are negative. There exists inverse relationship between real depreciation of domestic currency and real consumption in the long run, but short run shows positive relation between them. The long run as well as short run dynamics of the model are significantly stable. Hence, income is a robust determinant of aggregate consumption. Real interest rate seems to generate substitution effects on consumption, and inflation rate evokes real balance effect on the aggregate consumption of Nepal further.